History of Suicidality and Pandemic Outcomes: Longitudinal Associations with Anxiety Symptoms, Depressive Symptoms, and Problematic Drinking - Jeremy W. Luk; Matthew F. Thompson; Laura A. Novak; Bethany L. Stangl; Melanie L. Schwandt; David Goldman; Vijay A. Ramchandani; Nancy Diazgranados (Psychiatric Research and Clinical Practice, 2024)
Objective Individuals with a history of suicidality may be especially vulnerable to the adverse impact of COVID‐related stressors, but this vulnerability has not been demonstrated. This study examined the longitudinal effects of suicidality history (ideation only or attempt vs. none) and interactions with COVID‐related stressors (e.g., work interruptions, childcare challenges, and financial stress) on anxiety symptoms, depressive symptoms, and problematic drinking. Methods Longitudinal data from 517 participants were drawn from the National Institute on Alcohol Abuse and Alcoholism Natural History Protocol and COVID‐19 Pandemic Impact on Alcohol Study. Lifetime history of suicidality was assessed using the clinician administered Columbia‐Suicide Severity Rating Scale. Multiple regressions tested the interaction between suicidality history and COVID‐related stressors on clinical outcomes. Results Compared to individuals without any history of suicidality (79.9%; n = 413), individuals with a history of suicide ideation only (14.5%; n = 75) and suicide attempt (5.6%; n = 29) had higher anxiety symptoms, depressive symptoms, and problematic drinking during the pandemic. Significant interaction effects showed the associations between COVID‐related stressors and mental disorder symptoms were stronger among individuals with suicide attempt history than individuals without suicidality history. Conclusions History of suicide attempt in combination with high COVID‐related stressors put individuals at the greatest risk for pandemic mental disorder symptoms. Individuals with suicide attempt history may have lower coping resources to handle COVID‐related stressors. Suicide risk assessment and intervention to increase cognitive flexibility and emotional regulation skills may help these individuals manage emotional distress experienced during the COVID‐19 pandemic and beyond.